2007
DOI: 10.1111/j.1365-2990.2007.00873.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of receptor tyrosine kinase signal transduction activity in chordoma

Abstract: Chordomas commonly express RTKs and activated signal transduction molecules. Although there were no statistically significant correlations between the expression of any of the markers studied and disease-free survival or tumour location, the results nonetheless indicate that chordomas may respond to RTK inhibitors or modulators of other downstream signalling molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
36
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 38 publications
5
36
1
3
Order By: Relevance
“…Weinberger et al claim that c-erbB2 immunoreactivity is seen in 7 cases out of 11 (17) while in the study of Fasig et al no reactivity by c-erbB2 is demonstrated although two different clones of this antibody being used (16). Our results are consistent with the study of Fasig et al…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Weinberger et al claim that c-erbB2 immunoreactivity is seen in 7 cases out of 11 (17) while in the study of Fasig et al no reactivity by c-erbB2 is demonstrated although two different clones of this antibody being used (16). Our results are consistent with the study of Fasig et al…”
Section: Discussionsupporting
confidence: 83%
“…In another study based on 29 cases, vertebral localization appeared to be a significant risk factor for recurrence (30). In a study by Fasig et al, no correlation was found between tumor localization and recurrence in 20 chordoma cases (16). We have not found a specific correlation between localization and recurrence in our study.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…As it is known that chordomas also express several other tyrosine kinase receptors including c-MET, PDGFR b and KIT, EGFR, Her2/ neu and TrK, which also activate the RAS/RAF/ MEK/ERK pathway, these should be considered candidates for the regulation of brachyury. [28][29][30][31][32] The occurrence of FGFR mutations is well documented in the literature, and these are associated in both neoplasia and developmental syndromes. The mutations implicated in the former include those in endometrial, gastric, urothelial and prostatic cancers, 21,[33][34][35][36][37] and many of the activating FGFR2 and FGFR3 mutations, recently reported in endometrial carcinomas, are identical to germline mutations known to cause syndromes, several of which give rise to skeletal abnormalities including the Apert Syndrome, Beare-Stevenson Syndrome, hypochondroplasia, achondroplasia and the SAD-DAN syndrome (see Supplementary Table 2 based on Catalogue of Somatic Mutations In Cancer (COSMIC).…”
Section: Discussionmentioning
confidence: 99%